Calcium-vitamin D supplementation; does it affect lipid profile of menopaused women with normal renal function? - Maryam Javadian; Shahla Yazdani; Karimollah Hajian-Tilaki; Roya Gharouei (Journal of Nephropharmacology, 2017)
Introduction: The association between dyslipidemia and cardiovascular disease in women has been proposed and many studies investigated calcium-vitamin D (CaD) supplementation and their effect on lipid concentrations. Objectives: This randomized single-blind study aimed to evaluate the effect of CaD supplementation on serum lipid levels of menopaused women with normal renal function. Patients and Methods: In this study, 100 women 50-75 years old with cholesterol of 200-239 mg/dL, triglyceride (TG) of 150-199 mg/dL, low-density lipoprotein (LDL-C) of 100-159 mg/dL and vitamin D level less than 30 ng/mL and normal glomerular filtration rate (GFR) (>90 mL/min/1.73 m2) were investigated. First, body mass index (BMI) and waist circumference were calculated. The patients were given CaD supplement tablets made by Tehran Shimi Pharmaceutical Manufacturing Co. twice-daily (containing 500 mg calcium and 200 IU vitamin D) before breakfast and before lunch for 6 months. Then, blood lipid levels were collected after 3 and 6 months and were compared with initial data. Results: One hundred women with average age of 62.76 ± 7.02 years and BMI of 27.98 ± 3.44 kg/m2 were enrolled. FBS, cholesterol, HDL-C and LDL-C of the patients significantly increased (P < 00.001) but the mean TG and LDL/HDL ratio significantly decreased (P < 00.001). Also, the difference in LDL/HDL ratio was not significant after 3 months, but it was significant after 6 months (P = 00.155 and P < 00.001, respectively). Conclusion: Supplemental CaD significantly increased HDL-C and decreased TG and LDL/HDL ratio. Thus, it is recommended in menopaused women.